2020
DOI: 10.1111/ijfs.14499
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and colour properties of apple jellies supplemented with inulin with various degrees of polymerisation

Abstract: The objective of this study was to analyse the influence of inulin with different degrees of polymerisation (DP values) and oligofructose preparation on physicochemical and rheological properties of apple jelly. It has been determined that both the addition of inulin (independently of DP) and oligofructose significantly modify the rheological and textural properties of the analysed desserts. Preparation with high DP results in increased moduli, preparation with moderate levels results in their decrease, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(32 reference statements)
1
4
0
Order By: Relevance
“…However, the authors state that the colour differences found are not only correlated with DP but also due to the interaction between inulin and other system components, as well as the technologies utilised in the production of this prebiotic. In agreement with the data obtained by Witczak et al (2020), our results suggest that the greater degree of polymerisation of inulin contributed to the different values of h and ΔE* for spray-dried powder 2, results that originated from the differences observed (P < 0.05) in a* and b* parameters.…”
Section: Spray-dried Powder Propertiessupporting
confidence: 92%
See 1 more Smart Citation
“…However, the authors state that the colour differences found are not only correlated with DP but also due to the interaction between inulin and other system components, as well as the technologies utilised in the production of this prebiotic. In agreement with the data obtained by Witczak et al (2020), our results suggest that the greater degree of polymerisation of inulin contributed to the different values of h and ΔE* for spray-dried powder 2, results that originated from the differences observed (P < 0.05) in a* and b* parameters.…”
Section: Spray-dried Powder Propertiessupporting
confidence: 92%
“…Complementing the values found for the Hue angle, this was also observed for the spray-dried powder 2. In the study of Witczak et al (2020), a higher ΔE* was found for samples containing inulin with a higher degree of polymerisation. However, the authors state that the colour differences found are not only correlated with DP but also due to the interaction between inulin and other system components, as well as the technologies utilised in the production of this prebiotic.…”
Section: Spray-dried Powder Propertiesmentioning
confidence: 92%
“…Though various studies have evaluated the impact of addition of each of the inulin and oligofructose individually on the growth of probiotic bacteria in synbiotic dairy products and their physicochemical composition (Al‐Shawi, 2020; Ghaderi‐Ghahfarokhi et al, 2020; Iriondo‐DeHond et al., 2020; Kariyawasam et al., 2021; Tayyebymoghadam & Ehsani, 2020), only a few studies analyzed the influence of inulin and oligofructose in combination on the physicochemical composition and sensory properties of food products mainly fruits (Witczak et al, 2020). To the best of our knowledge, limited studies have considered the utilization of combination of inulin and oligofructose and the evaluation of their efficacy to stimulate the growth of indigenous probiotic strains in the synbiotic yoghurt.…”
Section: Introductionmentioning
confidence: 99%
“…Inulin is considered to be a promising substitute for fruit dessert recipes because it can outstandingly modify the rheological and textural properties of apple jellies. 45 High DP results in increased moduli, moderate DP results in their decrease, while low DP levels initially decrease and then increase the values of both moduli. Further, the gel strength and cohesion were subject to a considerable increase with inulin addition.…”
Section: Applicationmentioning
confidence: 93%